Learning in a Reggio-Inspired Reuse Center - Lauren Lantz-Helm; Will Parnell (Networks: An Online Journal for Teacher Research, 2010)
What would children’s learning look like in the Child Development Center’s Re-Use Center if teachers, parents, and children could collaborate around the learning? This action research collaboration between a professor and a graduate student/teacher, examines the process the graduate student/teacher goes through as she documents the re-use center narratives of a small group of young children. A re-use center is likened to Reggio Emilia, Italy’s Remida Center as a repository for found, rescued and repurposed materials. This center finds new meanings for discarded items destined for landfills and incinerators. The findings reveal stories of language, literacy and social development as well as explore how intentional collaboration can enhance project planning. Conclusions reveal that big questions for teachers, rich dialogue in reuse contexts for learning, and flexibility with participants are essential to collaborative learning in the reuse center.